The scope of the participant's perspective in Joseph Raz's Theory of Law - Gaido, Paula Marina (2012)
This article explores Joseph Raz's methodological thesis about the conceptual priority of the participants of legal practices in the understanding of law. In particular, it contends that given the participant's conceptual priority in the understanding of law we must conclude that legitimate authority is a necessary property of law. It argues that to maintain that a claim to legitimate authority is the necessary property of law, and not legitimate authority itself, as Raz does, we must abandon the participant's perspective. It defends that Raz introduces his thesis of the claim to legitimate authority of law without further justification, and deprives it from support from a methodological point of view.